Studies on urban park cooling effects and their driving factors in China: Considering 276 cities under different climate zones. (15th August 2022) - Zhou, Yi; Zhao, Haile; Mao, Sicheng; Zhang, Guoliang; Jin, Yulin; Luo, Yuchao; Huo, Wei; Pan, Zhihua; An, Pingli; Lun, Fei
Abstract: Continuous urbanization and future climate change will bring serious urban heat island effects (UHIs) in cities, resulting in more intensive urban heat risks. It has attracted more attentions to mitigate UHIs, and urban parks have been regarded as one promising measurement, due to their cooling effects. However, present studies have not comprehensively explored urban park cooling effects (PCEs) at the regional scale, especially considering park landscapes and climate zones. In order to better present PCEs and their driving factors, 12, 780 urban parks in 276 Chinese cities were crawled, and they were across seven Köppen-Geiger climate zones. All these urban parks were clustered into four categories of the Green Park, the Blue Park, the Mixed Park and the Grey Park, according to their landscapes. Our studies presented that PCEs increased a little with the latitude in China, and limited differences of PCEs existed between megacities and other cities. The Green Park and the Blue Park presented better cooling effects in all climate zones, but there existed great differences among different climate zones. The cold desert climate zone (BWk) had better PCEs than other climate zones, due to its higher potential evaporation. For most climate zones, park landscape factors presented larger contributions to PCEs than other factors of park surrounding conditions and local climate, and thus park landscapes played the dominant role in PCEs. Although the Blue Park with less park area (0.27–0.68 ha) could have better cooling efficiency than the Green Park (0.30–0.55 ha) in most climate zones, local water resources and economic costs should be considered for urban park planning. Climate change could have great impacts on PCEs, and 42% of all urban parks will present less PCEs in future. Considering multiple services, it is of high importance to tradeoff between their PCEs and recreation services for future urban planning and urban parks structure. Graphical abstract: Image 1 Highlights: Park cooling effects increased with the latitude. The cold desert climate zone had better park cooling effects. Park landscapes played a key role in park cooling effects in most climate zones. The Blue Park with less park area could have better cooling efficiency. Roughly 42% of all urban parks would present less PCEs due to climate change.